A century of mountaineering: race, class and the politics of climbing Table Mountain, 1890 – 1990 - Khan, Farieda (Acta Academica: Critical views on society, culture and politics, 2018)
Mountaineering in Cape Town was first practised as a sport by the colonial elite during the late 19th Century. This historical review of two mountain clubs analyses the linkages between race, class and mountaineering in Cape Town, South Africa. The origins of mountaineering are inextricable from the racial hierarchy of colonial society, which was founded upon discrimination, segregation and unequal power relations between black and white. This is evident in the development of the exclusively white Mountain Club of South Africa – an organisation deeply embedded in the privileged political establishment. Similarly, the racialised power relations of the 20th Century would be reflected in the club’s distant, exclusionary and paternalistic relationship with local black mountaineers and the Cape Province Mountain Club. Through an exploration of the developmental trajectories of these two, at one time racially exclusive, mountaineering clubs, their interaction with each other and their navigation of the contemporary socio-political context, this paper tells the history and politics of climbing Table Mountain between 1890 to 1990.